Cognitive changes and their impact on functioning at work: A qualitative study on women with breast cancer / Maryam Hafsah Mohammed Selamat - Maryam Hafsah, Mohammed Selamat (2016)
Cancer-related cognitive impairment or chemobrain is an increasingly acknowledged after-effect of cancer treatment. It has occurred in 15 to 70 percent of patients. However, evidence of its presence is limited along with limited published articles on it. The aim of this study is to understand the phenomenon of chemobrain from qualitative perspectives. The objectives therefore are: i) to review qualitative studies that explored the lived experience of chemobrain among breast cancer survivors, with particular attention to its impact on daily living and quality of life; ii) to explore the perspectives from a) post-chemotherapy working women on the level of awareness and perceived impact of cognitive changes, and suggestions for suitable management b) health care providers (oncologists) on chemobrain issues. METHODS: This is a two-stage study to explore and to understand the phenomenon of chemobrain in cancer survivors. In stage one, a qualitative systematic review using meta-ethnography approach and conducted with selected keywords. 10 electronic databases were searched. Stage two involves a) four focus groups interview with breast cancer survivors (n= 17) and b) an in-depth interview with oncologists (n = 12). Thematic analysis and constant comparative method were used to explore the common and unique themes across participants. RESULTS: In stage one study: data was extracted from seven selected papers and concepts were analysed using a meta-ethnography approach. Final synthesis resulted in four new order interpretations: i) the chemobrain struggle, ii) the substantial impact of chemobrain on life domains, iii) struggling to self-manage, and iv) ‘thankful yet fearful’ representation. In stage two study: the focus group discussion with the survivor revealed five themes. These were: i) varying level of awareness, ii) debilitating impact on work iii) social climate at the workplace and iv) trying to self-manage. Meanwhile, the thematic analysis of in-depth iv interviews with the oncologists revealed three main emerging themes: i) lack of awareness ii) beliefs and attitudes on chemobrain and iii) future direction on chemobrain. DISCUSSION: Awareness of cognitive changes was context-dependent in healthcare settings and cultural contexts which appeared as strong determinants. Subjects verified the existence of chemobrain, but healthcare providers mis-recognised, under-recognised, and even negated it, perhaps due to its uncertain aetiology. Qualitative findings from the review as well as from focus groups with survivor confirmed that chemobrain brain impacted the work functioning of survivors. The lack of awareness, beliefs on the conception of the chemobrain between both patients and healthcare providers contributed to the poor acknowledgement and a lack of striving to address chemobrain in cancer survivors. CONCLUSION: The current literature on findings from the lived experiences of women’s experiences of chemobrain and the in-depth qualitative findings provided a consistent report that chemobrain is real and persistent with detrimental impacts on work functioning (manifested as constant struggles) and on the quality of life of breast cancer survivors.